Sistema de manejo y sanidad en explotaciones ganaderas de Córdoba. - Navarrete Suárez, Mario G.; Trheebilcock Perna, Enrique; Orjuela Mesa, Jaime E. (Instituto Colombiano Agropecuario - ICA, 2018)
Ganadería bovina